2006
DOI: 10.1080/10473289.2006.10464512
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Ammonia Concentrations and Emissions from Agricultural Land and Liquid Surfaces: A Review

Abstract: Aerial ammonia concentrations (C g ) are measured using acid scrubbers, filter packs, denuders, or optical methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 74 publications
2
22
0
1
Order By: Relevance
“…A number of studies using dynamic chamber measurements (Aneja et al 2000;Blunden and Aneja 2008) have led to higher emission estimates than found by micrometeorological measurements (Harper and Sharpe 1998;Harper et al 2000Harper et al , 2004bHarper et al , 2010. Doorn et al (2002b) pointed out that studies with dynamic chambers led to emission factors 2.3 times higher than studies with micrometeorological techniques, while others (Shah et al 2006;Rochette et al 1992;Harper 2005;Harper et al 2010; stated that chamber techniques are not even suitable for developing emission factors as they create conditions at the water surface that overestimate NH 3 emissions. Based on all of the evidence (Harper et al 2000(Harper et al , 2004bWeaver et al 2012) and discussions regarding the physical chemistry of highly anaerobic systems (van Clemput 1972(van Clemput , 1997, it seems very plausible that NH 3 emissions from lagoons are lower than indicated by current emission factors and a significant fraction of N is emitted as N 2 .…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies using dynamic chamber measurements (Aneja et al 2000;Blunden and Aneja 2008) have led to higher emission estimates than found by micrometeorological measurements (Harper and Sharpe 1998;Harper et al 2000Harper et al , 2004bHarper et al , 2010. Doorn et al (2002b) pointed out that studies with dynamic chambers led to emission factors 2.3 times higher than studies with micrometeorological techniques, while others (Shah et al 2006;Rochette et al 1992;Harper 2005;Harper et al 2010; stated that chamber techniques are not even suitable for developing emission factors as they create conditions at the water surface that overestimate NH 3 emissions. Based on all of the evidence (Harper et al 2000(Harper et al , 2004bWeaver et al 2012) and discussions regarding the physical chemistry of highly anaerobic systems (van Clemput 1972(van Clemput , 1997, it seems very plausible that NH 3 emissions from lagoons are lower than indicated by current emission factors and a significant fraction of N is emitted as N 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, as it is used indoors, temperature is not affected by solar radiation (Shah et al, 2006b). A chamber with these characteristics may thus be deemed appropriate to measure emissions from animals and manure.…”
Section: Chamber Design and Operationmentioning
confidence: 99%
“…Chambers offer four advantages: easy replication, comparison of treatments, there are no site restrictions and are relatively inexpensive (Shah et al, 2006b). The chambers usually enclose a small area (0.1 to 0.2 m 2 ), which may be a restriction when studying heterogeneous emitting sources, for example, open field emissions (Meissinger et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, as it is used indoors, the temperature is not affected by solar radiation (Shah et al, 2006b). For these reasons, a chamber with these characteristics may be deemed appropriate to measure emissions from animals and manure.…”
Section: Chamber Design and Operationmentioning
confidence: 99%
“…Chambers offer four advantages: easy replication, comparison among treatments, no site restrictions, and relatively inexpensive cost (Shah et al, 2006b). These chambers usually enclose a small area (0.1 to 0.2 m2), which may be a restriction when studying heterogeneous emitting sources, for example, open field emissions (Meissinger et al, 2001).…”
Section: Introductionmentioning
confidence: 99%